GUTIERRÃ‰Z DAN TEOLOGI PEMBEBASAN - Mali, Mateus (Jurnal Orientasi Baru, 2016)
Liberation theology emerges as a movement within the Chatolic Church in Latin America in the 1950s and 1960s. This movement is principally as a moral reaction to the poverty and social injustice in the region. Gustavo GuttiÃ©rrez gives the movement its name: â€œtheology of liberationâ€Â (1971) that attempts to interpret Scripture through the plight of the poor. This essay deals with the GuttiÃ©rrez concept of theology of liberation. From GutiÃ©rrez, we learn that doing theology means to seek to interpret the actions of the Catholic Church and the teachings of Jesus Christ from the perspective of the poor and disadvantaged.